Viability Measurement of Hydropower Projects - Krishna Prasad Ojha,; Surendra Kumar Uprety,; Khubi Ram Acharya, (Pravaha, 2023)
Evaluating the viability of hydropower projects involves a comprehensive examination of costs and benefits. Economic analysis extends to broader impacts, such as fuel diversification, market advantages, production cost savings, job creation, and improved reliability. Benefit-cost analysis compares monetary costs and benefits, including direct and indirect community effects. This study has used literature survey method to provide insights into projected and actual outcomes, supported by guidelines from institutions like ADB, UNIDO, and the World Bank. Financial benefits of hydropower projects involve optimizing energy output and revenue from Power Purchase Agreements. Economic benefits include fuel diversification, market impacts, navigation, tourism, water supply, and tax revenues. Costs related to physical properties, structures, and resettlement are evaluated using the Price Quantity (PQ) method, while rental income and business losses are assessed through opportunity cost analysis. The loss of crops and trees is evaluated based on expected yields. This approach ensures a thorough understanding of both financial viability and broader economic impacts.